AÇÃO DA CLORPROMAZINA EM RINS DE CÃES SUBMETIDOS À ISQUEMIA E REPERFUSÃO - MENEZES, Liliana Borges de (2009)
Renal ischemia is present in different situations such as vascular or kidney surgery and also in renal transplantation. The aim of this study was to evaluate the renal function in dogs submitted to ischemia and reperfusion after chlorpromazine application. Twelve adult mongrel dogs were distributed into two groups with six animals: group A - ischemia and reperfusion without previous administration of chlorpromazine; group B - ischemia and reperfusion treated previously with chlorpromazine. Blood and urine samples were harvested in four different times: before ischemia, at the beginning of reperfusion, 120 minutes after of reperfusion and every week until postsurgical day 28 in order to check the possible ischemia/reperfusion late effect. Renal function was evaluated by clinical examination, serum urea and creatinine levels and urinary GGT activity. PU/CU and urinary activity of GGT were more sensitive for detecting acute tubular injury then routine urine examination, because these variables showed earlier alterations. It was not possible to verify the chlorpromazine protective action through urinalysis, creatinine and urea serum levels, excretion of GGT urinary and urine protein:creatinine ratio.